(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The essay gives a sharp outline of the recent Italian law ruling body donation to science after death, as a personal choice exclusively founds on a conscious and free act of will. The statute, however, has not been met its aim, lacking of supporting the donor in making his consent fully effective. Indeed, as one of the highest displays of human solidarity, this issue would have required a balance between scientific research interests and individual autonomy protection.